2015
DOI: 10.1158/2159-8290.cd-15-1285
|View full text |Cite
|
Sign up to set email alerts
|

RNF2 E3 or Not to E3: Dual Roles of RNF2 Overexpression in Melanoma

Abstract: Summary RNF2/Ring1B is amplified and overexpressed in numerous tumors and contributes to tumorigenicity, however the biological importance is poorly understood. Surprisingly, the role of RNF2 in tumorigenesis and invasion can be separated into catalytically-independent and catalytically-dependent processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…It is executed through ubiquitin-activating enzymes E1, ubiquitin-conjugating enzyme E2, and ubiquitin ligase E3 [88,89]. According to previous studies, dysregulation of E3 ubiquitin enzymes and impropriety targeting of the proteins by E3 leads to many disorders, such as cancer metastasis, including GC [90][91][92][93]. Thus, blocking the ubiquitin-proteasome pathways administers a novel approach to treating carcinomas [94].…”
Section: Discussionmentioning
confidence: 99%
“…It is executed through ubiquitin-activating enzymes E1, ubiquitin-conjugating enzyme E2, and ubiquitin ligase E3 [88,89]. According to previous studies, dysregulation of E3 ubiquitin enzymes and impropriety targeting of the proteins by E3 leads to many disorders, such as cancer metastasis, including GC [90][91][92][93]. Thus, blocking the ubiquitin-proteasome pathways administers a novel approach to treating carcinomas [94].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the noncatalytic function of RNF2 also provides important insight to potential therapies. MEK1-dependent phosphorylation of RNF2 leads to the formation of alternative complexes containing the histone demethylase KDM6A and the histone acetyltransferase EP300, which activate downstream target genes such as CCND2 [108].This suggests the possibility of using RNF2 inhibitors in combination with either MEK or EP300 inhibitors to target both tumor growth and metastasis [109].…”
Section: Rnf2mentioning
confidence: 99%
“…According to the authors [ 10 ] the effect of the LTBP2 down-regulation was stimulation of the TGFβ signaling pathway which in turn promoted invasiveness of melanoma cells. The same study demonstrated also that RNF2 supports anchorage independent proliferation of melanoma cells through up-regulation of cyclin D2 due to activation of CCND2 gene [ 11 ]. Another noteworthy conclusion of Rai et al [ 10 ] was that the spectrum of genes influenced by RNF2 depends on pre-existing chromatin promoter states of the genes.…”
Section: Introductionmentioning
confidence: 99%